31. Does continuous positive airway pressure treatment affect autonomic nervous system in patients with severe obstructive sleep apnea?. Issue 12 (December 2017) - Rocchi, C.; Placidi, F.; Liguori, C.; Lauretti, B.; Pisani, A.; Mercuri, N.B.; Izzi, F.
Abstract : To evaluate whether Continuous Positive Airway Pressure treatment (CPAP) affect autonomic nervous system (ANS) in patients with severe obstructive sleep apnea (OSAS). We compared de novo OSAS patients, OSAS patients on chronic CPAP treatment and controls using the Scales for Outcome in Parkinson disease-Autonomic (SCOPA-AUT) questionnaire. All groups underwent autonomic function tests including head-up tilt test (HUTT), Valsalva maneuver, deep breathing, handgrip and cold face test. Twelve untreated OSAS, 17 OSAS on CPAP and 14 controls were studied. SCOPA-AUT total score was significantly higher in untreated OSAS compared with controls. The baseline values of systolic and diastolic blood pressure were significantly increased in untreated OSAS and in CPAP patients respectively, compared to controls. At HUTT, diastolic blood pressure changes were significantly higher in controls compared to both OSAS groups. Untreated OSAS showed a reduced response at deep-breathing compared to controls. Both OSAS groups had a significant reduction of reflex bradycardia at cold-face test. Treated and untreated OSAS patients complaint subjective autonomic symptoms reinforcing the close relationship between sleep and ANS. Cardiovascular reflexes indicate a tendency to hypertension and a reduced sensitivity to stimuli during wakefulness in both groups, suggesting a high risk of cardiovascular and cerebrovascular diseases.